1995
DOI: 10.1007/bf00019287
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal contamination of Lake George (Uganda) and its wetlands

Abstract: Lake George is a shallow equatorial lake in Uganda which, around its fringe, has a wetland designated as a Ramsar site of high international importance . A nearby copper mine has caused serious metal pollution of the surrounding land. Results show that heavy metals from mine waste, particularly copper and cobalt, are entering Kahendero Swamp, part of the Ramsar wetland, and contaminating the lake . In the lake, metals pass along the food chain . The distribution of metals in the wetland and possible modes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
0
18
1
1
Order By: Relevance
“…Cu is easily mobilised and transported in solution to downstream locations including the Lake (Lwanga, et al, 2003). In the lake, metals are likely to enter into the food chain and enter the fish tissues (Denny, et al, 1995). In Kampala, Pb concentration in the effluents from a battery manufacturing industry was 5600 µg/L with corresponding Zn and Cu concentrations of 390 µg/L and 800 µg/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Cu is easily mobilised and transported in solution to downstream locations including the Lake (Lwanga, et al, 2003). In the lake, metals are likely to enter into the food chain and enter the fish tissues (Denny, et al, 1995). In Kampala, Pb concentration in the effluents from a battery manufacturing industry was 5600 µg/L with corresponding Zn and Cu concentrations of 390 µg/L and 800 µg/L, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Simpson (1996, 1997a, b), Polprasert et al (1996), and Scholes et al(1998) reported that roots of wetland plants are very important in wastewater purification and phytostabilisation of metal contaminants, followed by stem and leaves. Barley et al (2005) and Denny et al (1995) also reported that metal uptake was higher in the roots.…”
Section: Introductionmentioning
confidence: 88%
“…Grill et al (1985) reported that excess heavy metals are bound to the cell wall by metathiolate formation through mercaptide complexes. Briggs et al (1961), Denny (1987), and Denny et al (1995), studied electron micrographs of Potamogeton crispes L. and Potamogeton pectinatus L. (submerged plants) tissues and reported that lead was taken from the sediments and translocated to leaf tips, dead regions, and lower older leaves. Sharpe and Denny (1976) and Welsh and Denny (1979) reported that most of the metal uptake by plant tissue is by absorption to anionic sites in the cell walls and the metals do not enter the living plant.…”
Section: Introductionmentioning
confidence: 99%
“…Other metals have not been so well studied, and there is a lack of information regarding aspects such as the effects of plants on the distribution of these metals. Chromium (Cr) in trivalent form, cobalt (Co), and nickel (Ni) are considered as essential elements when present at trace levels; however, when present at excessive levels, these metals are toxic to living organisms, and are considered as contaminants to soil, surface water, and groundwater (Denny et al, 1995;KabataPendias & Pendias, 2001). Co and Ni are released into the atmosphere from the combustion of coal and oil and from metal-processing operations, whereas Cr is released by various sources, of which the main ones are industrial waste and municipal sewage sludge (Kabata-Pendias & Pendias, 2001).…”
Section: Introductionmentioning
confidence: 99%